(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The changes in the social-economic and state structure of Rome, carried out at the time of the Principal (1st century BC – 3rd century AD), i.e. at the transition from republican to monarchial state order, inevitably reflected on the Roman criminal justice. Indeed, at this initial time of the so-called Roman classical law, the remains of the former cognition procedure still existed and dominated the so-called Quaestiones perpetuae or Quaestiones ordinariae (jury courts), but, despite this, in the early period of the Empire, new forms of criminal courts were introduced. In this paper, due to the limited available space, we will focus mainly on organization and jurisdiction of the Roman Senate – as aristocratic state body of the nobility, and the trials that took place in front of it in this turbulent period of Roman state and legal history, with particular regard to the rule of the second emperor Tiberius (ruled 14–37 AD).